Evaluation and Analysis of Trends in Socio-Economic Development of Selected Groups of the European Union Member States and Their Regions in the Context of the EU Expansion - Semigulina Irina B. (Bìznes Inform, 2016)
The article carries out analysis and evaluation of trends in socio-economic development of regions of the «older» and «newer» EU Member States for the period of 2003–2012. The level of socio-economic development of the regions has been evaluated within the specified group of the Member States as well as in comparison with average European indicators. Efficiency of the regional policy of the European Union has been analyzed on the basis of comparative analysis of selected indicators of socio-economic development of regions of selected groups of the EU Member States together with the dynamics of the level of inequality of their development in terms of expansion and structural changes of the European Union. The possibility of application of the best practices for Ukraine has been considered